Empowerment of Village Women through Strengthening The Structural Role of The Family Empowerment and Welfare (PKK) in Lok Lahung - Nur'aini, Fatwa; Rahmia, Sovia Husni; Syarifuddin, Syarifuddin; Triyono, Sigit; Ilhami, M. Ridha (The Innovation of Social Studies Journal, 2026)
This study examines the structural role of the PKK in efforts to empower women in Lok Lahung Village. The purpose of this research is to identifyand analyze the structural role of the PKK, the programs carried out, and the various challenges faced in the process of empowering village women.This study uses a qualitative method with a case study approach. Data collection techniques include in-depth interviews, participatory observations,and documentation studies with informants consisting of PKK administrators, community leaders, and women involved in empowerment activities.Data analysis is carried out through triangulation of sources and techniques to obtain comprehensive data validity. The results of the study showthat the PKK's organizational structure which is systematic with the division of labor plays a role in empowering women through four main functions.First, the adaptation function is realized through adjusting the PKK program to the social and economic needs of village women. Second, the goalattainment function is reflected in the implementation of leadership capacity building programs and organizational management for PKKadministrators. Third, the integration function can be seen from the role of the PKK in providing a space for social and cultural participation thatstrengthens solidarity and social networks of village women. Fourth, the latency function is realized through the internalization of productive gendervalues, norms, and roles that support the sustainability of women's empowerment. However, this study also found a number of structuralchallenges, including the limitations of leadership regeneration, uneven distribution of responsibilities, and the organization's dependence on certainfigures. Therefore, in order to optimize its empowerment role, PKK organizations in Lok Lahung Village need to restructure more inclusive andadaptive to the needs of local women, as well as strengthen collaboration with the village government and other empowerment institutions.